Anterior lens capsule rupture following minor blunt trauma with a past history of minimal change glomerulopathy - Lau, Stephen V Lau V; Kansakar, Prerana; Limbu, Ben (Nepalese Journal of Ophthalmology, 2014)
Introduction: Few cases have been reported describing anterior lens capsule ruptures secondary to blunt trauma. Case: We present an unusual case of anterior lens capsule ruptures following minor trauma from a human elbow with a two-year history of minimal-change glomerulopathy in a 17-year-old male. In addition to having bilateral posterior subcapsular cataracts, he developed an anterior subcapsular cataract underlying the anterior lens rupture in the right eye. He was managed conservatively. Observations: The current case differs from those of the existing literature in terms of the characteristics of the physical insult and the eye on presentation. We suggest there could be a predisposing anterior capsule weakness secondary to the minimal-change glomerulopathy or the associated drug therapy, but there needs to be more evidence to confirm or refute our claim. Conclusions: Anterior lens capsule may rupture following minor trauma on a background of minimal-change glomerulopathy. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11714 Nepal J Ophthalmol 2014; 6 (12): 230-233